Role of surgical drains in orthopedics - Aditya Goel; Shivendra Singh; Navin K Shukla (Journal of Orthopaedic Diseases and Traumatology, 2023)
Introduction: The use of drains in orthopedic practice has been affected by the concept of evidence-based medicine, which is accepted as the standard of care for all surgical or medical practices. This concept questions all care processes that cannot be backed by evidence to be beneficial to the patient. There have been a large number of multi-center meta-analytical studies that have found drains to be of little or no benefit in trauma and orthopedic surgeries. As a result of these studies, there are few situations where drains are routinely used, such as calcaneal fractures in developed countries. Even major procedures such as total knee and arthroplasties are being performed without drains. We aim to investigate whether similar evidence can be found in our practice. Materials and Methods: This sounds like the description of a prospective randomized controlled trial studying the use of drains in certain types of surgical procedures. The study population consisted of 86 patients matched for sex and type of injury, and they were assigned to either a group that used drains or a group that did not use drains during their operations. The study aimed to observe and compare the rates of complications, such as hematoma, drain migration, infection, and inadvertent drain stitching, between the two groups. Results: Eighty-six major orthopedic operations were studied. There was no evidence of the occurrence of complication arising from nonuse of drains in the undrained group. Those patients whose wounds were drained had no need for drain change, thus making the wound care less eventful. Conclusion: Wound drains can help reduce tissue swelling in the postoperative period, but there is no significant difference in infection rates, hematoma, or seroma formation between drained and undrained wounds.